Evaluasi Komunikasi: Studi Kasus Pelaksanaan Program Pemberdayaan Masyarakat Penggiat Anti Narkoba Oleh BNN Jakarta Timur - Sylvia Roennfeld; Sophia Bernadette (SOSIO DIALEKTIKA : JURNAL ILMU SOSIAL HUMANIORA, 2021)
The problem of drug abuse and trafficking is increasingly becoming a problem for every country worldwide, including Indonesia. DKI Jakarta, as the state capital, ranks third nationally in narcotics abuse, with a trial use prevalence rate reaching 4.9%. In this study, researchers will focus on evaluating communication programs carried out through technical guidance carried out by BNN for anti-drug activists in the educational environment. We utilized the four stages of program planning by Cutlip, Center and Broom, to get a picture of the situation, program planning and form of communication, which will elaborate further on aspects of communication evaluation based on the Yardstick evaluation model.. Keywords: BNN, Community Empowerment, Drugs, Public Relations, Yardstick Evaluation